Social Support and Leadership Effectiveness: Insights from Pesantren Bahrul Ulum Jombang - Shofiyulloh, Mohammad; Rahmawati, Desi; Santosa, Heru; Sugara, Zidni (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
Purpose – This research explores the pivotal role of social support in augmenting leadership efficacy at Pesantren Bahrul Ulum Jombang, a prominent Islamic educational establishment in Indonesia. Design/methods/approach – Adopting a qualitative case study approach, data was accrued through semi-structured interviews and observation. Rigorous measures, including data triangulation and member-checking, were instituted to bolster the study's credibility and authenticity. Findings – Four core categories of social support emerged: Emotional, Instrumental, Informational, and Appraisal. These types, while distinct, collaboratively underpin leadership potency. Specifically, Emotional support markedly amplifies self-assuredness and judicious decision-making, whereas Instrumental support optimizes operational processes. Informational support is pivotal in tactical problem resolution and discerning decision-making, while Appraisal support consolidates the institution's reputation and garners community faith. Research implications/limitations – These insights have profound ramifications for understanding leadership within Islamic educational contexts, especially in Indonesia. To fortify educational leadership, stakeholders and policy framers are urged to weave social support paradigms into overarching educational directives. Nonetheless, the research's concentration on one establishment and the absence of extended temporal data serve as its primary constraints.